Spectrum of phenomena of multiple myocardial contractions during each single cardiac cycle - Gavranović, Željka, liječnica; Miličević, Goran (2009)
Abstract: The phenomenon of multiple myocardial contractions during each single cardiac cycle, triggered by a single sinus node impulse, is the most intriguing echocardiographical topic among detectible modalities of irregular kinetics of interventricular septum. Tissue Doppler imaging based methods gave proofs of active contractions in cases presented herein. Broad spectrum of this phenomenon, which can be found both in healthy subjects and in patients is presented. Forms of multiple myocardial contractions during the same cardiac cycle presented in this analysis are: secondary systolic contraction, postsystolic and late postsystolic contraction, multiple (three- and fourfold) contractions with combination of secondary systolic and postsystolic contraction, and combination of regular systolic, secondary systolic or postsystolic contraction with pre-contraction as a part of possible preexcitation. Explanation of mechanism generating these phenomena could be found in possible existence of accessory, concealed slow pathways of cardiac conduction system
Bibliografija: 9 jed
Sažetak
Keywords: Višestruka kontrakcija miokarda -- Srčani ciklus -- Metoda tkivnog Dopplera